1988
DOI: 10.1111/j.1464-410x.1988.tb04275.x
|View full text |Cite
|
Sign up to set email alerts
|

Ureteric Obstruction Secondary to Pelvic Actinomycosis

Abstract: Pelvic actinomycosis is a rare cause of ureteric obstruction. The diagnosis is usually difficult and often only apparent after histological examination of an operative specimen. The following case led us to consider the aetiology, clinical findings and to review the management of reported cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Brown responded well to tetracycline therapy alone (25). Another 45-year old female, with IUD use for more than 13 years, presented with bilateral ureteric obstruction secondary to a large pelvic mass involving the uterus, tubes, ovaries, and rectum (26). Fulton et al reported 2 cases with ureteric obstruction, secondary to IUD-associated Pelvic actinomycosis (27).…”
Section: Discussionmentioning
confidence: 99%
“…Brown responded well to tetracycline therapy alone (25). Another 45-year old female, with IUD use for more than 13 years, presented with bilateral ureteric obstruction secondary to a large pelvic mass involving the uterus, tubes, ovaries, and rectum (26). Fulton et al reported 2 cases with ureteric obstruction, secondary to IUD-associated Pelvic actinomycosis (27).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation can result in a frozen pelvis, making surgery treacherous with ill‐defined tissue planes and distorted anatomy. Ureteric obstruction due to the inflammatory mass leading to hydronephrosis has been well described 9 . Thus the efficacy of conservative treatment with antibiotics is welcomed.…”
Section: Discussionmentioning
confidence: 99%
“…The infection has a long latent period with unspecific clinical signs, and is easily confused with a malignant neoplasic process, 9ÿ11 given the capacity of Actinomyces to produce fibrosis in the tissues and to cause intestinal as well as ureteral obstruction. 12 In general, most authors concur that the best treatment for pelvic actinomycosis is the combination of surgery and specific antibiotherapy. 3).…”
Section: Discussionmentioning
confidence: 99%
“…7 In the context of her illness our patient presented compression of the right ureter, an infrequent complication in this type of infection as demonstrated by the scarcity of cases of ureteral obstruction referred to in the relevant literature. 12 In general, most authors concur that the best treatment for pelvic actinomycosis is the combination of surgery and specific antibiotherapy. 13 Actinomyces may be treated with penicillin, being characterized by its positive response to the latter, although some cases of negative response to this antibiotic have been described.…”
Section: Discussionmentioning
confidence: 99%